(untitled) (Voice of Teacher, 2021)
Social security is a fundamental human right to which every individual has been entitled as a member of the society. It is the programs developed to reduce the vulnerability of an individual. The main objective of this paper is to examine on effectiveness of social security system in Nepal. This study follows to analyze the effectiveness Social Security Allowance among the beneficiaries especially for senior citizen, widowed, fully disabled and partially disabled. The implication of the study is to strengthen the social security programs in Nepal. This study is based on primary data collection in terms of use of the allowance and use of it to maintain the social status. This study reveals that social security allowance have been used for the fulfilment of basic personal needs.